Reproductibilité, validité et sensibilité d`un test de répétition de sprints chez des jeunes footballeurs - Selmi, M.A.; Elloumi, M.; Hambli, M.; Sellami, M.; Haj Yahmed, M.; Haj Sassi, R. (Science & Sports, 2016)
Purposes: To assess the reliability, criterion and construct validity of multiple repeated-sprint sets test (RSS) in young soccer players. Methods: To investigate the reliability and criterion validity of the RSS test, 24 young soccer players who belong to a professional team club took part in this study. They performed the RSS test twice, both vertical and horizontal jumps, the 20-m maximal shuttle run test and the yoyo intermittent recovery test. To examine the construct validity of the RSS test, we recruited 25 other young soccer players who belong to a regional team club to complete the RSS test. Results: Reliability of total sprint time (TST) and best sprint time (BST) of the RSS test was very good, with intraclass correlation coefficient greater than 0.80, typical error of measurement < 5% and small limits of agreement. Horizontal jumps and yoyo performance were the only determinants of TST. Areas under the receiver operating characteristics curves (ROC) for TST, BST and fatigue index were 0.909, 0.855 and 0.803, respectively. These findings suggest that the RSS test is reliable and valid field test for assessing the ability to repeated-sprint sets performance in young soccer players.